Peningkatan Personality Development dan Keterampilan Komunikasi Bagi Mahasiswa Baru Di Perguruan Tinggi Swasta - Mulyadi, Mulyadi; Sudianto, Sudianto; Fadlilah, Andi Hidayatul (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Most successful people, they already know their potential. Currently students who continue to enter public and private universities are Generation Z who are open to advanced technological developments. But apart from that, a term emerged that is currently going viral among Genarasi Z itself, namely the Remaining People. Many of them are comfortable and lazy to do self-development. The method used in this service is Small Group Discussion, which is giving a case to be discussed at the small group level. Problem Based Learning is a model that trains and develops the ability to solve problems oriented to authentic problems from actual life, to stimulate higher order thinking skills. Discovery Learning is a method of giving study or research assignments to students with the aim of being able to find the answers to the expected targets themselves. Students can take lessons from the stories and stories told, so that it is easier to recognize their potential. It is very important for students to see and hear firsthand the stories and experiences of successful people, so that they can motivate themselves, of course, in a style that keeps up with developments.